Energy lost study for the steam and solvent assisted gravity drainage process, using reservoirs with Brazilian northeast characteristics (Research, Society and Development, 2024)
In Brazil, especially in the Northeast, there are still reservoirs containing heavy oils that are being operated by smaller companies that need to produce the fields, reducing production costs. There are different processes to recover heavy oil, one of which is steam and solvent assisted gravity drainage process, which uses two parallel horizontal wells, where the injector is placed above the producer. In this process, a solvent can be used with the steam, to try to reduce the steam rate injected. Process is carried out by injecting a hydrocarbon additive in low concentration together with steam. Steam contributes with the heat to reduce oil viscosity and solvent helps with miscibility, reducing the interfacial tension. The main force acting in this process is gravitational. The mobility of the displaced fluid is then improved, which may imply at an increase of oil recovery. In this study, a semi-synthetic model was analyzed, with average characteristics of the Brazilian northeast, where there is heavy oil in onshore reservoirs. Several simulations were carried out using a commercial oil reservoir thermal simulation software, where the influence of some operational parameters on oil recovery and energy in the reservoir were verified. The main objective of this study was to find a distance between producer and injector wells that allows reducing heat losses to the overburden and underburden when solvent and steam are injected into the process. It was found an optimal vertical distance to improve oil recovery.